Efficacy of endoscopic ultrasound-guided biliary drainage of malignant biliary obstruction: a systematic review and meta-analysis of randomized controlled trials - Yousaf Zafar; Hafsa Azam; Muhammad Abdullah Bin Azhar; Fabeeha Shaheen; Syed Sarmad Javaid; Laila Manzoor; Muaaz Masood; Rajesh Krishnamoorthi (Clinical Endoscopy, 2025)
Background/Aims Malignant biliary obstruction is a major clinical challenge. We assessed the efficacy of endoscopic ultrasound-guided biliary drainage (EUS-BD) compared with that of endoscopic retrograde cholangiopancreatography biliary drainage (ERCP-BD) or percutaneous transhepatic biliary drainage (PTBD). Methods We searched for randomized controlled trials comparing EUS-BD with ERCP or PTBD in treating malignant biliary obstruction. Using random-effects models, we synthesized risk ratios (RRs) and weighted mean differences (WMDs) with 95% confidence intervals (CIs). A subgroup analysis was performed using a comparator (ERCP or PTBD). Results EUS-BD significantly reduced the risk of stent dysfunction (RR, 0.46; 95% CI, 0.33–0.64), with consistent results in subgroup analysis for ERCP (RR, 0.54; 95% CI, 0.35–0.84) and PTBD (RR, 0.37; 95% CI, 0.22–0.61). It also lowered the risk of post-procedure pancreatitis (RR, 0.24; 95% CI, 0.07–0.83) and reduced tumor ingrowth or overgrowth risk (RR, 0.27; 95% CI, 0.11–0.65), even when compared to ERCP alone (RR, 0.28; 95% CI, 0.11–0.70). EUS-BD demonstrated a lower risk of adverse events compared to PTBD (RR, 0.37; 95% CI, 0.14–0.97) and reduced length of hospital stay (WMD, –1.03; 95% CI, –1.53 to –0.53) when compared to ERCP. Conclusions EUS-BD outperformed ERCP-BD and PTBD in reducing stent dysfunction, postprocedural pancreatitis, and tumor ingrowth or overgrowth.